The role of Psychological and Religious Counseling in achieving Psychological Adjustment among female high school adolescent - yahia, ahlam (Journal of Social Sciences and Humanities, 2020)
This study aimed at identifying the level of psychological adjustment and the role of psychological religious counseling in achieving psychological adjustment among female high school adolescents, where it tried to answer the following questions : ✓ What is the level of psychological adjustment among female high school adolescent? ✓ Is Psychological and religious counseling a role in achieving Psychological adjustment among female high school adolescents ? To answer study questions and test its hypothesis ,we used the descriptive analytical method .as for the study sample ,it consisted of (152) female high school adolescents ( 76 of them attend koranic school and 76 don’t). they were chosen by a simple random sampling procedure. as for the data collection , we used Psycho-social Adjustment scale of Suhair Ibrahim (2004) where the number of distributed copies reach (250) copy, where as the retrieved ones reach the number of (152)with response rate of (60.8%) We have been using: the Arithmetic Mean, Standard Deviation and t-test for differences. The study yielded the following results : ✓ The female high school adolescents have a high level of psychological adjustment. ✓ Psychological and religious counseling a role in achieving psychological adjustment among female high school adolescents And This sudy concluded to a set of proposals, which are : ✓ -Training experts on the practise of psychological and religious counseling because of its benefits that serve human resource in society. ✓ -The importance of training on psychological and religious counseling and its various arts in the curriculum of Educational departments ,especially with Practitioners in the field ,and embed it in the curriculum ✓ The need to pay attention to the religious education of children ✓ Helping adolescents with study problems by explaining the causes of the problem and working to eliminate it ✓ Educate adolescents about the need to think and analyze before convincing other’s opinions ✓ Helping adolescents achieve their social and psychological adjustment